Long-term mortality after admission to hospital for trauma: A review. (July 2013) - Niven, Daniel J; Kirkpatrick, Andrew W; Ball, Chad G; Laupland, Kevin B
Trauma is associated with significant acute morbidity and mortality. However, advances in the delivery of trauma care have resulted in considerable improvements in the short-term mortality from trauma. Recent studies have shown that survivors of trauma are at significant risk of delayed long-term mortality that is above that expected for a similar uninjured cohort of patients. Few studies have provided a detailed analysis of the determinants of this increased risk of death, and even fewer publications have examined the causes of death in these patients. This information is relevant because an increased number of patients will survive their injuries as acute trauma care continues to improve. It may also highlight opportunities for interventions that reduce the risk of delayed death in a population of patients that is generally young and healthy at the time of injury. As such, this article will review the literature on the long-term mortality rate and its determinants among patients who are hospitalized for severe injuries.